2007
DOI: 10.1103/physrevlett.98.133601
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Transport due to Light Scattering

Abstract: Using experiments and theory, we show that light scattering by inhomogeneities in the index of refraction of a fluid can drive a large-scale flow. The experiment uses a near-critical, phase-separated liquid, which experiences large fluctuations in its index of refraction. A laser beam traversing the liquid produces a interface deformation on the scale of the experimental setup and can cause a liquid jet to form. We demonstrate that the deformation is produced by a scattering-induced flow by obtaining good agre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 21 publications
(18 reference statements)
1
38
0
Order By: Relevance
“…3 The energy necessary to expel the jet can be originated by, for instance, physicochemical processes produced by surfactants 4 or thermal effects induced by the energy of concentrated irradiation. 5 Extensional flows constitute a remarkable class of techniques in which a force is applied on a drop to stretch an interface until a thin fluid ligament is obtained. A variety of driving forces can be used to expel the fluid jet.…”
Section: Introductionmentioning
confidence: 99%
“…3 The energy necessary to expel the jet can be originated by, for instance, physicochemical processes produced by surfactants 4 or thermal effects induced by the energy of concentrated irradiation. 5 Extensional flows constitute a remarkable class of techniques in which a force is applied on a drop to stretch an interface until a thin fluid ligament is obtained. A variety of driving forces can be used to expel the fluid jet.…”
Section: Introductionmentioning
confidence: 99%
“…Hole et al (2005) trapped and propelled 250 nm diameter gold spheres; individual particle trajectories exhibited velocities up to 500 lm/s, showing promise for high throughput sorting. Recently Schroll et al (2007) have demonstrated bulk transport of liquid with mesoscopic spatial variations in refractive index under radiation pressure.…”
Section: Evanescent Field Trapping and Propulsionmentioning
confidence: 99%
“…For example, a cylindrical dripping liquid jet was produced by light scattering in a microemulsion and the dripping rate was theoretically predicted [20]. The fluid motion due to the light scattering was also observed in a fluid layer with a flat interface [21], where a toroidal fluid recirculation was produced by a vertically incident laser beam. The scattering force induced an interface deformation that was found to be on the same order of magnitude as the deformation induced by the radiation pressure.…”
Section: Introductionmentioning
confidence: 99%